Listening effort and fatigue among cochlear implant users: a scoping review - Philips, Cato; Jacquemin, Laure; Lammers, Marc J. W.; Mertens, Griet; Gilles, Annick; Vanderveken, Olivier M.; Van Rompaey, Vincent (Frontiers in Neurology, 2023)
In challenging listening situations, speech perception with a cochlear implant (CI) remains demanding and requires high levels of listening effort which can lead to increased levels of listening-related fatigue.The body of literature on these topics increases as the number of CI users rises. This scoping review aims to provide an overview of the existing literature on listening effort, fatigue and listening-related fatigue among CI users and the measurement techniques to evaluate them. The Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) Statements were used to conduct the scoping review. The search was performed on PubMed, Scopus and Web of Science to identify all relevant studies. In total, 24 studies were included and suggests that CI users experience higher levels of listening effort when compared to normal hearing controls using scales, questionnaires and electroencephalogram measurements. However, executing dual-task paradigms did not reveal any difference in listening effort between both groups. Uncertainty exists regarding the difference in listening effort between unilateral, bilateral and bimodal CI users with bilateral hearing loss due to ambiguous results. Only five studies were eligible for the research on fatigue and listening-related fatigue.Additionally, studies using objective measurement methods were lacking. This scoping review highlights the necessity for additional research on these topics. Moreover, there is a need for guidelines on how listening effort, fatigue and listening-related fatigue should be measured to allow for study results that are comparable and support optimal rehabilitation strategies.